Analyzing journal abstracts written by Japanese, American, and British scientists using Coh-Metrix and the Gramulator - Philip M. McCarthy; Charles Hall; Nick D. Duran; Maki Doiuchi; Yuko Fujiwara; Benjamin Duncan; Danielle S. McNamara (The ESPecialist: Research in Language for Specific Purposes, 2011)
This interdisciplinary study comprises two complementary analyses on a corpus of journal abstracts written in English by American, British, and Japanese scientists. The fi rst analysis uses the computational tool Coh-Metrix to assess text at the discourse level. The second analysis uses the computational tool the Gramulator to compare the frequency of n-grams across the three sources of abstracts. The Coh-Metrix and Gramulator analyses both suggest signifi cant differences between all three varieties of English. The greatest differences were apparent when comparing abstracts written by Japanese and English speakers; however, a number of differences were also apparent when comparing the British English and American English varieties. The results lend weight to the conclusion that native-English speakers (reviewer, editor, or reader) of either the British or American variety may interpret Japanese-English texts as lacking in key areas of the proto-typical style of the English register. Our findings provide information for instructors, course developers, and scientists on how and where text might be modifi ed in order to facilitate the production of more native-English-like representations.